2014
DOI: 10.1371/journal.pone.0113665
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Use and Body Mass Regulation among Warblers in the Sahel Region during the Non-Breeding Season

Abstract: Migratory birds face significant challenges across their annual cycle, including occupying an appropriate non-breeding home range with sufficient foraging resources. This can affect demographic processes such as over-winter survival, migration mortality and subsequent breeding success. In the Sahel region of Africa, where millions of migratory songbirds attempt to survive the winter, some species of insectivorous warblers occupy both wetland and dry-scrubland habitats, whereas other species are wetland or dry-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Temperature may influence nestling mass indirectly, by affecting insect activity/availabilityand thus parental provisioning ratesover a daily timescale, or over the lifetime of a nestling, as discussed above. Overall, invertebrate activity and abundance tend to be reduced under cooler conditions (Bryant 1975, Turner 1983, Jenni-Eiermann et al 2008; a higher body mass under cool conditions is consistent with the use of strategic deposition of fat reserves as a buffer against starvation under conditions with low or unpredictable food availability (Witter et al 1994, 1995, Ratikainen & Wright 2013, Vafidis et al 2014.…”
Section: Discussionmentioning
confidence: 58%
“…Temperature may influence nestling mass indirectly, by affecting insect activity/availabilityand thus parental provisioning ratesover a daily timescale, or over the lifetime of a nestling, as discussed above. Overall, invertebrate activity and abundance tend to be reduced under cooler conditions (Bryant 1975, Turner 1983, Jenni-Eiermann et al 2008; a higher body mass under cool conditions is consistent with the use of strategic deposition of fat reserves as a buffer against starvation under conditions with low or unpredictable food availability (Witter et al 1994, 1995, Ratikainen & Wright 2013, Vafidis et al 2014.…”
Section: Discussionmentioning
confidence: 58%
“…coastal wetlands, Inner Niger delta, wetlands in eastern Mauritania), which dry out later and may suppress the adverse effects of the dry season for several months (Studds & Marra, 2005). Such least arid habitats may sustain vegetation and associated insect life for longer in the dry season, enabling kestrels to spend a large part of their non-breeding period at these sites (Zwartz et al, 2009; Vafidis et al, 2014). While the kestrels’ longitudinal itinerary movements differ from the predominantly latitudinal movements of other locust-specialists and aerial hunters (swifts, Akesson et al, 2012; swallows, Norevik et al, 2019, harriers, Trierweiler et al, 2013; Schlaich et al, 2016), east-west movements within the Sahel have also been reported for other species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Tree species usually found on seasonal floodplains should attract more birds since there are many more insects in wetlands than in drylands (e.g. Vafidis et al 2014). 3.…”
mentioning
confidence: 99%